A study on the chloride diffusion behavior of blended cement concrete in relation to aggregate and ITZ. (30th October 2019) - Wu, Kai; Long, Jiangfeng; Xu, Linglin; De Schutter, Geert
Highlights: The relative importance of ITZ and bulk matrix to chloride diffusion was evaluated. Natural diffusion tests were performed on varied aggregate volume content and size. Using slag blocks chloride penetration effectively. The reduction of diffusivity is mainly due to the improvement of bulk matrix. Abstract: The reinforcement corrosion caused by chloride is one of the main threat to structural concrete exposed to marine environment or de-icing salts. The penetration of chloride is highly determined by the pore structure. In this study, the effect of pores on chloride diffusion of concrete made with varied aggregate volume fraction and size distribution was evaluated from the interfacial transition zone (ITZ) point of view. The pore structure was analyzed by using mercury intrusion porosimeter (MIP) in relation to the binder compositions and aggregates. Results show that the diffusivity decreases firstly with increasing aggregate content from 0 to 0.2, and followed by a slight increase in the pure cement group. The diffusivity increases for the specimens made with coarser aggregate. The addition of appropriate amount of blended materials could mitigate the influence of aggregate on the chloride diffusion. Increasing aggregate volume content or reducing the mean particle size, which increase the total intruded volume of pores superior to 100 nm, contribute most to the increase of total porosity. Considering the effect of limestone filler and slag on the pore structure within ITZ and bulk cement paste, the reduction in chloride diffusivity could be mainly due to the densification of the matrix.